Agrippan pyrrhonism and the challenge of disagreement - Machuca, Diego Emanuel (2015)
This paper argues for the following three claims. First, the Agrippan mode from disagreement does not play a secondary role in inducing suspension of judgment. Second, the Pyrrhonist is not committed to the criteria of justification underlying the Five Modes of Agrippa, which nonetheless does not prevent him from non-doxastically assenting to them. And third, some recent objections to Agrippan Pyrrhonism raised by analytic epistemologists and experimental philosophers fail to appreciate the Pyrrhonist's ad hominem style of argumentation and the real challenge posed by the mode from disagreement.